Emulsion-structured pectin-based edible films with whey protein and short-chain dietary fibers for geranylgeraniol encapsulation and strawberry preservation - Adela Cristina Martinez Urango; Maria Angela A. Meireles; Eric Keven Silva (Food Chemistry: X)
This study reports the design and characterization of emulsion-structured pectin-based edible films incorporating whey protein concentrate (WPC), short-chain prebiotic fibers (fructooligosaccharides, FOS; galactooligosaccharides, GOS; and xylooligosaccharides, XOS), and annatto seed oil as a source of geranylgeraniol. The formulation strategy combined citrus pectin with WPC and fibers to enhance the structural and functional properties of films while improving oil stabilization. The film-forming emulsions were processed by thermosonication to promote biopolymer dispersion and stable droplet incorporation. All films exhibited desirable technological features, including high encapsulation efficiency of geranylgeraniol (≥70 %). They also showed strong UV–vis light barrier properties and improved thermal stability in fiber-containing formulations. FTIR and fluorescence analyses indicated protein-carbohydrate interactions, although covalent Maillard-type conjugation was not confirmed through SDS–PAGE analysis. Dietary fiber addition influenced film microstructure, water vapor permeability, and crystallinity without compromising overall mechanical integrity, except for GOS films, which showed lower tensile strength. When applied as coatings, emulsions containing annatto seed oil effectively delayed strawberry spoilage during refrigerated storage, demonstrating their potential for extending shelf life. These findings highlight the relevance of emulsion-structured edible films as active packaging systems for delivering lipophilic bioactives and improving postharvest preservation of fresh produce.